2015
DOI: 10.1007/s00068-015-0507-y
|View full text |Cite
|
Sign up to set email alerts
|

Open reduction and internal fixation versus percutaneous transverse Kirschner wire fixation for single, closed second to fifth metacarpal shaft fractures: a systematic review

Abstract: PurposeOpen reduction and internal fixation (ORIF) of single, closed metacarpal shaft fractures is increasingly preferred over closed reduction and percutaneous fixation (K-wire). The aim of this systematic review is to determine whether the preference for ORIF can be substantiated based on the available literature regarding the functional outcome and complications after surgery.MethodsA systematic review was performed using a computer-based search on MedLine and Embase, following the preferred reporting items… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
39
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(44 citation statements)
references
References 21 publications
3
39
2
Order By: Relevance
“…This finding is consistent with the literature demonstrating better outcomes with pinning versus plating of fifth metacarpal neck fractures specifically. 2,11 Fractures treated with percutaneous pinning were immobilized an average of nearly 2 weeks longer than those treated with plate or screw fixation. However, in this series, prolonged immobilization did not contribute to changes in ultimate TAM, stiffness, need for therapy, or need for revision surgery.…”
Section: Discussionmentioning
confidence: 99%
“…This finding is consistent with the literature demonstrating better outcomes with pinning versus plating of fifth metacarpal neck fractures specifically. 2,11 Fractures treated with percutaneous pinning were immobilized an average of nearly 2 weeks longer than those treated with plate or screw fixation. However, in this series, prolonged immobilization did not contribute to changes in ultimate TAM, stiffness, need for therapy, or need for revision surgery.…”
Section: Discussionmentioning
confidence: 99%
“…The incidence of our complications appears to be lower compared to other frequently used techniques such as plate fixation and transverse pinning [3,5,8]. Bone-healing disorders after surgical treatment of metacarpal shaft fractures in general are rare.…”
Section: Discussionmentioning
confidence: 94%
“…Functional limitations are more frequently encountered, probably due to postoperative adhesions or scar tissue. The recently published systematic review of Greeven et al provides a clear overview of the literature and complication rates of both transverse pinning and plate fixation of metacarpal shaft fractures [3]. Just like intramedullary fixation, transverse pinning is characterized by minimal softtissue injury, but shows a high incidence of (pin tract) infections up to 25%.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We therefore showed that locking plate in combination with two crossed K-wires could decrease the secondary displacement in volar angulation compared with fixation with locking plate alone in previous study 11 . However, percutaneous K-wire fixation could also lead to an increase in surficial infection and irrigation of skin 12 . In addition, pin tract infection was also a major complication after K-wire fixation 13 .…”
Section: Introductionmentioning
confidence: 99%